KESEJAHTERAAN ANAK TERKAIT HAK ATAS PERLINDUNGAN DARI LINGKUNGAN YANG MEMBAHAYAKAN DI LOKALISASI PROSTITUSI GANG BOKER, JAKARTA TIMUR: Children's Welfare Related To The Right To Protection From A Harmful Environment In The Localization Of Boker Gang Prostitution, East Jakarta - Khanza Poetri Ferdyan; Maria Silvya Elizabeth Wangga (Jurnal Hukum PRIORIS, 2024)
Every child has the same rights, namely the right to welfare. According to Law no. 4 of 1979 Child welfare is "a system of life and living for children that can guarantee their normal growth and development, both spiritually, physically and socially". Children are said to be prosperous if the child's basic rights have been fulfilled optimally. One of the rights that must be fulfilled is the right to protection from a dangerous environment as stated in Law no. 4 of 1979 concerning Child Welfare Article 2 Paragraph 4 "Children have the right to protection against the environment which can endanger or hinder their normal growth and development". To fulfill children's welfare, child welfare efforts are needed. This welfare effort is carried out by the child's parents, the community and the government. However, this is different from the condition of children in the Boker Ciracas Gang Prostitution Localization, where children's rights have not been fulfilled optimally, especially the right to protection from a dangerous environment.